Case report: A fatal outcome from co-infection of COVID-19 and dengue in the western region of Jeddah, Saudi Arabia - Al-Nazawi, Ashwaq M.; Al-Zahrani, Ali A.; Qadir, Anjum; Alghamdi, Rana; Tambo, Ernest; Alsahafi, Abdullah (Frontiers in Public Health, 2022)
Introduction Co-infection of coronavirus disease 2019 (COVID-19) and dengue may coexist, as both viruses share similar laboratory and clinical features, making diagnosis and treatment challenging for health care professionals to prescribe, negatively impacting patient prognosis, and outcomes. Results and discussions Both cases were positive for PCR and X-ray laboratory investigation at clinical examination, confirming COVID-19 and dengue co-infection, admission, and better management in referral hospitals are presented and discussed. The timeline provides detailed cases of situational analysis and the medical actions taken, as well as the outcomes. Conclusion Both co-infection cases' (patients) health conditions had a poor prognosis and diagnosis and ended with undesired outcomes. Scaling up dual mosquito-vector linked viral diseases surveillance in understanding the transmission dynamics, early diagnosis, and the timely and safe monitoring of case management in clinical and hospital settings nationwide is paramount in curbing preventable co-infections and mortality.